DIGITAL PAYMENT SYSTEMS ON THE CONSUMPTIVE BEHAVIOR OF UNIVERSITY STUDENTS IN D.I.Y WITH FINANCIAL RISK AS A MEDIATING VARIABLE - Alaya Lasendra; Sukirno (SOSIOEDUKASI, 2026)
The development of e-commerce and digital payment systems has changed transaction patterns and student consumption behavior. The ease of access and speed of transactions offered have the potential to encourage consumptive behavior, particularly through increased financial risk. This study aims to analyze the effect of e-commerce and digital payment system adoption on student consumptive behavior in the Special Region of Yogyakarta (D.I.Y) with financial risk as a mediating variable. This study uses a quantitative approach with a survey method involving 260 students who actively use e-commerce and digital payment systems. Data analysis was performed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that the adoption of e-commerce does not have a significant direct effect on consumptive behavior, while digital payment systems have a significant effect on the consumptive behavior of students. Financial risk was found to mediate the effect of e-commerce adoption on consumptive behavior, but did not mediate the effect of digital payment systems on consumptive behavior. The R-square value shows that e-commerce adoption and digital payment systems simultaneously explain some of the variation in students' consumptive behavior and financial risk. These findings confirm that financial risk plays an important role in explaining students' consumptive behavior in the digital age.